Sistem Informasi Penjualan dan Stok Barang Berbasis WEB : (Studi Kasus CV. Bumen Jaya Group) - Mutiara Kartika; Endang Wahyuningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to design and implement a web-based sales and stock information system to improve the efficiency and accuracy of data management in a retail company. The main problem is manual recording which causes data inaccuracy and late reporting. The method used is Research and Development with the Waterfall model, as well as black box testing and the System Usability Scale (SUS) questionnaire. The results of the study show that the system successfully provides real-time stock data and sales reports, minimizes recording errors, and increases user satisfaction. This system supports faster and more accurate managerial decision making. It is recommended that companies carry out periodic system maintenance and provide training to users to maximize system utilization. Further research can develop sales data analysis features and integration with financial systems.